Fast and effective embedded systems design : applying the ARM mbed - Toulson, Rob (Newnes, 2012)
A hands-on introduction to the field of embedded systems; A focus on fast prototyping of embedded systems; All key embedded system concepts covered through simple and effective experimentation; An understanding of ARM technology, one of the world's leaders; A practical introduction to embedded C; Applies possibly the most accessible set of tools available in the embedded world. This book is an introduction to embedded systems design, using the ARM mbed and C programming language as development tools. The mbed provides a compact, self-contained and low-cost hardware core, and the on-line compiler requires no download or installation, being accessible wherever an internet link exists. The book further combines these with a simple "breadboard" approach, whereby simple circuits are built up around the mbed, with no soldering or pcb assembly required. The book adopts a "learning through doing" approach. Each chapter is based around a major topic in embedded systems. The chapter proceeds as a series of practical experiments; the reader sets up a simple hardware system, develops and downloads a simple program, and immediately observes and tests the outcomes. The book then reflects on the experimental results, evaluating the strengths and weaknesses of the technology or technique introduced, explores how precise the link is between theory and practice, and considers applications and the wider context. The only book that explains how to use ARM's mbed development toolkit to help the speedy and easy development of embedded systems. Teaches embedded systems core principles in the context of developing quick applications, making embedded systems development an easy task for the non specialist who does not have a deep knowledge of electronics or software All key concepts are covered through simple and effective experimentation.